Efficacy of Potassium Citrate Solution in the Treatment of Renal Microlithiasis in Children 1 Month to 15 Years-old - Mohajeri, Saeed; Emami, Elham; Choopani, Roya; Malekpour, Afsaneh; Mousavi, Razieh (Journal of Pediatric Nephrology, 2022)
Abstract Background and objective: The present research aims to determine efficacy of potassium citrate solution in the treatment of renal microlithiasis in children one month to 15 years old in Shahrekord Pediatric Nephrology Clinic. Methodology: In this clinical trial study, 60 children aged 1 month to 15 years referred to Shahrekord Pediatric Nephrology Clinic who had one or two (microlithiasis) less than 3 mm in ultrasound; They were included in the study by available sampling. Children were randomly divided into 2 groups receiving placebo (water) and receiving potassium citrate solution. After 3 months, the number and size of stones and the consequences of stones were recorded in both groups and analyzed using SPSS software and relevant statistical tests. Results: Out of 60 children studied, 34 were male (56.7%) and 26 were females (43.3%) with a mean age of 61.62 47 47.54 months. After 3 months of intervention, the mean number and size of stones in each group had a significant decrease (P <0.001) and this amount was lower in the group receiving potassium citrate than the group receiving placebo, but this difference was not statistically significant (<0.05). P). Also, the consequences of kidney stones in both groups were similar and there was no significant difference (P <0.05). Conclusion: The results of this study showed that potassium citrate solution has no effect on the treatment of one or two microlithiasis in children and in these patients the use of supportive therapy is still sufficient. Keywords: Kidney stones, Microlithiasis, Children, Potassium citrate